2020
DOI: 10.21272/jes.2020.7(2).c1
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Carbon Coatings: Structure, Morphology, and Mechanical Properties

Abstract: Boron-doped carbon coatings have been produced by a method combining the deposition of a pulsed carbon plasma coating and a boron flow formed as a result of the evaporation of a boron target by pulsed YAG: Nd3+ laser irradiation. Phase, chemical composition, structure, and mechanical properties of composite boron-carbon coatings have been determined. Changes in the coatings’ roughness depending on the boron concentration have been established using atomic force microscopy. It has been shown that the grain size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(64 reference statements)
0
5
0
1
Order By: Relevance
“…During this time, the alloying elements' carbides and nitrides do not have time to grow to full sizes which inhibits further nitrogen diffusion into the metal. The presence of carbon and alloying elements [42] increases lattice defects and accelerates diffusion [43].…”
Section: Experimentally Determining the Thickness Of The Hardened Lay...mentioning
confidence: 99%
“…During this time, the alloying elements' carbides and nitrides do not have time to grow to full sizes which inhibits further nitrogen diffusion into the metal. The presence of carbon and alloying elements [42] increases lattice defects and accelerates diffusion [43].…”
Section: Experimentally Determining the Thickness Of The Hardened Lay...mentioning
confidence: 99%
“…Different brands of stamped steels are used to make radial forging machines. Steels used for heat-deforming dies must have high mechanical properties [21] (strength and toughness) at elevated temperatures and high scale resistance and heat resistance, i.e., the ability to withstand repeated heating and cooling without the appearance of hot cracks [22]. Steels must also have high wear resistance and thermal conductivity for industrial heat transfer transmitted by the workpiece [23][24][25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various factors were reported to affect the hole quality parameters in CFRP/Ti alloy stacks, including drill bit wear rate [ 6 , 25 , 26 , 27 , 28 , 29 ], cutting tool coating [ 4 , 15 , 22 , 26 , 30 , 31 , 32 ], cutting parameters [ 10 , 11 , 14 , 33 , 34 ], drill bit geometry [ 8 , 21 , 35 , 36 ], dynamic characteristics of CFRP [ 37 ], drilling strategies, and techniques, namely one-shot drilling of the stack [ 10 , 11 , 14 , 22 , 33 , 35 , 38 , 39 , 40 , 41 ], stepped bit geometry drilling [ 8 , 21 ], pilot hole drilling [ 42 ], cryogenic drilling [ 43 , 44 ], minimal quantity lubrication (MQL) [ 29 , 45 ], helical milling [ 9 , 46 ], and drilling with core drill [ 47 ]. In such a way, it can be summarized that one-shot drilling of CFRP/Ti alloy stacks is still a mainstream technology of manufacturing holes studies; we concluded that the most promising factors to improve the hole quality are the cutting parameters of the one-shot drilling strategy.…”
Section: Introductionmentioning
confidence: 99%